npj Veterinary Sciences - Kaler, Jasmeet; Fanget, Nicolas; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Veterinary Sciences is an Open Access journal publishing on all aspects of veterinary sciences, including farm or commercial use animals, wild animals and companion animals, animal behaviour, welfare epidemiology, preventive and therapeutic medicine, One Health and animals in society. npj Veterinary Sciences considers all aspects of basic, applied and clinical veterinary science. The journal covers a broad range of topics including but not limited to: Farm animals Wild animals Companion animals Animal behaviour Animal welfare Infectious diseases Epidemiology Preventive and therapeutic medicine Flock and herd management One Health Veterinary social sciences.
Keywords: Veterinary medicine; Veterinary microbiology; Veterinary medicine; Animal welfare$1 (BMoral and ethical aspects.s; Veterinary Science; Veterinary Microbiology; Veterinary Clinical Medicine; Animal Ethics